PENAFSIRAN KEISLAMAN DI LAMAN YOUTUBE: STUDI KASUS TAFSIR LISAN GUS IZZA SADEWAA - M. Ulil Abshor (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2022)
Gus Izza's oral exegeses on YouTube with the subject of Gus Izza and the object of interpretation aboutIslam including faith, monotheism, useful people and role’s ulama’ are the main basis of legitimacy that focuses on the transformative aspect of human life. Transformative aspect that are formed from the intersection of the Qur'an with communication media come from two things communicator (speaker) and communicant (audience). Communicator produced orality conveyed through YouTube, while communicants give birth to the transformative aspect of understanding human consciousness. The approach used in this research is interpretive descriptive. The theory used in analyzing the interpretation of Gus Izza on YouTube is the theory of orality and structure of Jean Piaget - Kuntowijoyo's quote -. Orality theory as the nature of human language that communicated without face to face directly. While the structure forms transformative aspect in the form of surface structure and deep structure. The results obtained reflect that Gus Izza's oral exegeses model is not a complete and complex interpretation, but an Islamic discourse that is based on the subject's understanding of Islam forming a dynamic and transformative human self-awareness. Dynamic form of surface structure and transformative form of deep structure